10+p=6

Simple and best practice solution for 10+p=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+p=6 equation:


Simplifying
10 + p = 6

Solving
10 + p = 6

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + p = 6 + -10

Combine like terms: 10 + -10 = 0
0 + p = 6 + -10
p = 6 + -10

Combine like terms: 6 + -10 = -4
p = -4

Simplifying
p = -4

See similar equations:

| F(x)=15 | | 101-9y=29 | | 7-4x=4+3x | | Y-60=-17//2(x-20) | | 42-2x=5 | | -2x-2=2x+14 | | 13-6x=7-8x | | 122/75 | | We+14=8(q+7) | | -31+a=-6 | | 5x^2-14+49=0 | | 3(x-1)-4(x-1)=36x+24 | | -8(x/2-y/4)= | | x+squrt(4x)-5=0 | | ln(4x-3)+ln(x+1)= | | -2(4a+3b)= | | -11+y=-31 | | 5+6log^2x=14 | | -1=3(3x-2) | | (3x^2y)(5x^2y^2-6xy+2)= | | (2x+20)(5x-20)=1200 | | 100-2x=50 | | -4/7x=32 | | (2x+20)(5x-20)= | | -6=6(w-9) | | 7+78m=39m+25 | | 2x-2+3x+12=12x+6 | | -10(s+3)=-51 | | x^2+0.714x-0.153=0 | | -(c-10)=3 | | 5x+14=-49-4x | | 3x-6/12=10 |

Equations solver categories